Structural changes of the Malaysian economy and its spatial incidence on regional economic growth - Mohit, Mohammad Abdul (Malaysian Institute of Planners, 2009)
The economy of Malaysia has undergone changes from its agricultural base to import-substitution during the 1960s and finally to export-orientation after 1968, associated with an influx of significant amount of direct foreign investment (DFI). These changes of the production base of the country led to concomitant changes in the structure of employment from agriculture to manufacturing and finally to services. Studies so far undertaken mostly concentrate on the macro aspect of this transformation process. No attempt has been made to study the structural changes of the national economy through analyzing the production/ employment structure of the regions/states of Malaysia. In spit of adopting and implementing a number regional development policies and strategies from 2MP, it is anticipated that the structural transformation has not been uniform across the different regions of the country. Therefore, this paper provides a spatial analysis of the structural changes in the structure of production and employment that has occurred across fourteen states of Malaysia. The study found that the economic growth process has been unequal across the 14 states of Malaysia, accentuating the regional disparities in income and employment growth. Both federal government development expenditure and private investments in different states of Malaysia have not been proportionate to their shares of national population and this partially explains the reason for the interregional differences of economic growth in the country.